The Role of Lectora Inspire Based Learning Media on the Achievement of Higher Order Thinking Skill: Literature Review - Shakila Zulima Marindra; Silvi Yulia Sari (Physics Learning and Education, 2023)
The use of technology in learning media is the goal of national education which requires educators to be able to master and adapt according to the times. Education must be held in an interactive, inspiring, fun, challenging, and motivating way for students to participate actively, and provide sufficient space for student’s initiative, creativity, and independence. This study aims to analyze the use of interactive learning media to improve students' Higher Order Thinking Skills (HOTS) in learning Physics. The research method used was a literature review conducted by reviewing several national and international articles related to the use of Lectora Inspire-based interactive learning media in improving students' HOTS abilities. The sample used was 31 journal articles. The results of this study indicate that the use of interactive learning media based on Lectora Inspire can improve students' Higher Order Thinking Skills (HOTS) in learning Physics.